2020
DOI: 10.1103/physreva.101.033410
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high-order harmonic generation in semiconductors by excitation with multicolor pulses

Abstract: We investigate high-order harmonic generation in ZnO driven by linearly polarized multi-color pulses. It is shown that the intensities of the harmonics in the plateau region can be enhanced by two to three orders of magnitude when driven by two-or three-color fields as compared with the single-color pulse excitation. By analyzing the time-dependent population in the conduction band as function of both the initial and the moving crystal momenta, we demonstrate that this remarkable enhancement originates from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…[55] it was considered valley-selective HHG in pristine graphene by using a combination of the two counter-rotating circularly polarized fields. For solid targets with an energy gap exposed to two-or three-color laser pulses [49,52,54] of parallel polarizations the enhancement of HHG has been shown in an analogy with the atomic HHG [46], where the HHG in the orthogonally polarized two-color field is suppressed. The latter is intu-itively clear in terms of a simple quasiclassical three-step model [28,29].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[55] it was considered valley-selective HHG in pristine graphene by using a combination of the two counter-rotating circularly polarized fields. For solid targets with an energy gap exposed to two-or three-color laser pulses [49,52,54] of parallel polarizations the enhancement of HHG has been shown in an analogy with the atomic HHG [46], where the HHG in the orthogonally polarized two-color field is suppressed. The latter is intu-itively clear in terms of a simple quasiclassical three-step model [28,29].…”
Section: Introductionmentioning
confidence: 98%
“…The HHG with different compositions of the driving laser pulses was addressed also for solid targets and nanostructures considering two distinct regimes. First, if the driving field consists of the fundamental wave and its harmonics [4,24,[49][50][51][52][53][54][55], and second, if one of the involved wave frequencies significantly higher than the other one [2,[56][57][58][59][60][61][62]. Two-color high-order wave mixing research reported so far has mainly been performed for gapped systems.…”
Section: Introductionmentioning
confidence: 99%
“…This argument has been supported by Duchateau et al [36] also for a band-dispersion system, α-quartz. However, although electron dynamics and high-harmonic generation has been extensively discussed in terms of the coupling between intraband and interband transitions for single-color cases [24,[26][27][28][37][38][39][40][41][42][43][44], its role in simultaneous two-color irradiation has been little studied. Thus, while increase in energy absorption and ablation efficiency by dual-color pulse irradiation appears to be quite general observation, a consensus has not been reached on its mechanisms, which possibly depend on materials and irradiation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various schemes have been explored intensively to increase the cutoff and intensity of harmonics in solids, such as the employment of solid Ar (or Kr) [33], the consideration of pre-acceleration [41], properly-doped semiconductor [42,43], etc. On the other hand, different compositions of incident pulses, such as two color or even three color, have been explored where the relative intensity, delay, carrier-envelope phase (CEP), and pulse shape can be adjusted to achieve better characteristics of resulting harmonic spectra [44,45,46,47,48]. In solids, further extend of harmonics to higher energy region requires intenser incident pulse to drive direct transitions from the highest valence band to higher-lying conduction bands.…”
Section: Introductionmentioning
confidence: 99%